Conversations with families of children with disabilities : insights for teacher understanding - Puig, Victoria; Recchia, Susan (b, 2021)
"Conversations with Families of Children with Disabilities creates a space for diverse families of children with disabilities to share their stories with pre-service and in-service teachers. Specifically designed for professionals preparing to work with families of children with disabilities, this text invites the reader to listen in as families reflect on their personal journeys in conversation with the authors. This powerful book helps educators develop a deeper understanding of families and enhance their capacity for authentic partnerships"--
Includes bibliographical references.
Keywords: Special education -- Parent participation; Special education -- Psychological aspects; Special education teachers -- Training of; Parent-teacher relationships